Incidence, Progression, and Patterns of Multimorbidity in Community-Dwelling Middle-Aged Men and Women - Shang, Xianwen; Peng, Wei; Hill, Edward; Szoeke, Cassandra; He, Mingguang; Zhang, Lei (Frontiers in Public Health, 2020)
Background Determining the incidence, progression and patterns of multimorbidity is important for the prevention, management and treatment of concurrence of multiple conditions. This study aimed to analyze major multimorbidity patterns and the association of the onset of a primary condition or combinations of a primary and a secondary condition with the progression to subsequent conditions. Methods We included 53,867 participants aged 45-64 years from the 45 and Up Study who were free of 10 predefined chronic conditions at baseline (2006-2009). The incidence of multimorbidity (coexistence of ≥2, ≥3, and ≥4 conditions) was identified using claims database until December 31, 2016. The primary, secondary, tertiary and quaternary condition for each participant was defined according to its temporal order of onset. Results During a mean 9-year follow-up, the cumulative incidence of primary, secondary, tertiary and quaternary condition was 49.6%, 23.7%, 9.0% and 2.9%, respectively. The time to develop a subsequent condition decreased with the accumulation of conditions (P<0.0001). Two concurrent cardiometabolic disorders (CMDs, 30.4%) and CMDs clustered with musculoskeletal disorders (15.2%), mental disorders (13.5%), asthma (12.0%) or cancer (8.7%) were the five most common multimorbidity patterns. CMDs tended to occur prior to mental or musculoskeletal disorders but after the onset of cancers or asthma. Compared with all participants who developed cancer as a primary condition, individuals who experienced mental disorders/neurodegenerative disorders and a comorbidity as cardiovascular disease, hypertension, dyslipidemia, diabetes, asthma, or osteoarthritis were 3.36 to 10.87 times more likely to develop cancer as a tertiary condition. Individuals with neurodegenerative disorders and a comorbidity as hypertension, dyslipidemia, osteoarthritis or asthma were 5.14 to 14.15 times more likely to develop mental disorders as a tertiary condition. Conclusions A high incidence of multimorbity in middle-aged adults was observed and CMDs were most commonly seen in multimorbidity patterns. There may be an accelerated ageing after a primary condition occurs. Our findings also reveal a potential preventative window to obviate the development of secondary or tertiary conditions.